Recent Trends in Nanoelectronic Device Fabrication - Abbas, Mohamed; Algahtani, Ali; Kessentini, Amir; Loukil, Hassen; Parayangat, Muneer; Ijyas, Thafasal; Salaheldin, Bushara; Mohammed, Abdul W. (Current Nanoscience, 2020)
Most current modern devices have micro dimensions. For engineers and manufacturers, it is now possible to manufacture completely remote devices in a modern way. To determine the critical points in measuring the dimensions for the manufacturing of devices, which is achieved in practice and at an appropriate cost, numerous studies have been conducted around the world. Researchers have attempted to develop a pragmatic approach to interface various nanoscale devices together and to study their focal points and disadvantages. The objective of this study is to focus on modern trends in the manufacturing of nanoscale devices. These trends are divided into the following five sections: development of tribotronic devices, nanodevice fabrication using two-dimensional materials, fabrication using carbon nanotubes (CNTs), on-chip nanodevice fabrication, and nanodevices based on photonics. In this study, the views on these trends and how to effectively apply them in the future are presented. To enhance the structure and features of nanowires inside a scanning tunneling microscope (STM) scanner, a novel view about the structure of nanowire is presented. These nanowires demonstrate unique metal properties that enable them to operate in multiple environments with high efficiency. Using these nanowires inside an STM scanner can improve their ability to withstand high pressure because their metal properties minimize the chances of breakage.
Keywords: photonics